Thermal Environment Assessment of Gas Stove Surroundings - Vörösné Leitner Anita; Kajtár László (Slovak Journal of Civil Engineering, 2018)
Residential kitchens with gas stoves are unique spaces inside dwellings.Occupants directly exposed to the combustion products and thermal effects of the stove. Applying a general model with the knowledge of describing parameters, designer could taken thermal aspects also into consideration in order to provide a save, healthy and comfortable environment in residential kitchens and homes. The aim of this study to develop this model and a new ventilation method. Results of field studies shows disadvantageous effect of kitchen exhaust unit during the operation of oven. However turbulence intensity was decreased from 123% to 25% , indoor temperature was increased by 3,7K in the occupied zone due to the forced air movement. PMV index remained within the recommended intervals (between -1,0 and +1.9), therefore it could be applied to evaulate thermal environment aroun the residential gas stove. Unpleasent effect of draught is not expected.